Envisioning New Productivity Tools for Domestic Information Work Environments - Cho, Janghee; Voida, Stephen (2020)
ABSTRACT The home will serve as a primary workplace for information workers for the foreseeable future due to the coronavirus pandemic. This fundamental change in the context of work suggests that HCI and CSCW researchers will need to more intentionally focus on exploring how to design productivity tools for domestic environments. While past work has examined productivity and well-being in the context of traditional offices, few studies have examined these ideas in the home. In this position paper, we propose a new way of designing productivity tools for the home in light of previous research on domestic technologies, productivity tracking tools in the office setting, and pluralistic notions of productivity. We argue that productivity tools should be designed to (1) help information workers critically reflect on their domestic and work-centric time management practices in order to build their own pluralistic perspective on productivity, and (2) to incorporate multiple temporalities. Keywords reflection, productivity, well-being, information worker, working from home, domestic technology, self-tracking, temporality ABOUT THE AUTHOR/S JANGHEE CHO University of Colorado Boulder janghee.cho@colorado.edu Janghee Cho (https://tmilab.colorado.edu/ janghee) is a Ph.D. student in Information Science at the University of Colorado Boulder. He is interested in understanding how people make sense of data and AI-driven technologies and systems to support critical reflection. STEPHEN VOIDA University of Colorado Boulder svoida@colorado.edu Stephen Voida (https://stephen.voida.com) is an Assistant Professor of Information Science at the University of Colorado Boulder, where he studies personal information management, mental health informatics, and ubiquitous computing. New Future of Work ’20, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).